An Analysis of Students’ Writing Essay Ability in English through Class Group Presentation on Fifth Semester of STKIP Paracendekia NW Sumbawa - Umar, Umar (e-Journal of Linguistics; Vol 15 No 1 (2021): ejl-JanuaryDO - 10.24843/e-jl.2021.v15.i01.p13, 2021)
This is a quantitative descriptive research. The objective of this research was to know the influence of class group presentation in improving the students’ writing essay of English language learning. The participants of this research were 11 of the fifth semester students of STKIP Paracendekia NW Sumbawa. Data collecting instrument used structurally arranged questionnaires, and written test. The data was analyzed by quantitative method. The data analyzed technique employed descriptive statistics through percentage techniques. The result of the research showed that there were 8 students or 72.73% gain in the best category level of skill, there were 3 students or 27.27% gain in good category level of skill , and the mean score was 81.27 in the level of best category . Data from questionnaire, 9 students with 81.82% stated they strongly agreed that the implementation of group class presentation more active during teaching and learning process of writing essay.